EDEM2 and OS-9 are required for ER-associated degradation of non-glycosylated sonic hedgehog - Tang, H; Huang, C; Zhuang, Y; Christianson, J; Chen, X (Public Library of Science, 2014)
Misfolded proteins of the endoplasmic reticulum (ER) are eliminated by the ER-associated degradation (ERAD) in eukaryotes. In S. cerevisiae, ER-resident lectins mediate substrate recognition through bipartite signals consisting of an unfolded local structure and the adjacent glycan. Trimming of the glycan is essential for the directional delivery of the substrates. Whether a similar recognition and delivery mechanism exists in mammalian cells is unknown. In this study, we systematically study the function and substrate specificity of known mammalian ER lectins, including EDEM1/2/3, OS-9 and XTP-3B using the recently identified ERAD substrate sonic hedgehog (SHH), a soluble protein carrying a single N-glycan, as well as its nonglycosylated mutant N278A. Efficient ERAD of N278A requires the core processing complex of HRD1, SEL1L and p97, similar to the glycosylated SHH. While EDEM2 was required for ERAD of both glycosylated and non-glycosylated SHHs, EDEM3 was only necessary for glycosylated SHH and EDEM1 was dispensable for both. Degradation of SHH and N278A also required OS-9, but not the related lectin XTP3-B. Robust interaction of both EDEM2 and OS-9 with a non-glycosylated SHH variant indicates that the misfolded polypeptide backbone, rather than a glycan signature, functions as the predominant signal for recognition for ERAD. Notably, SHH-N278A is the first nonglycosylated substrate to require EDEM2 for recognition and targeting for ERAD. EDEM2 also interacts with calnexin and SEL1L, suggesting a potential avenue by which misfolded glycoproteins may be shunted towards SEL1L and ERAD rather than being released into the secretory pathway. Thus, ER lectins participate in the recognition and delivery of misfolded ER substrates differently in mammals, with an underlying mechanism distinct from that of S. cerevisiae.